2014
DOI: 10.1001/jamaoto.2013.6143
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal Negative Pressure Wound Therapy for Optimizing Pharyngeal Reconstruction

Abstract: Intraluminal negative pressure wound therapy is feasible and safe. Future research should be conducted to determine its potential in optimizing pharyngeal reconstruction in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 43 publications
1
26
0
1
Order By: Relevance
“…In patients undergoing treatment for fistula closure, 15 had prior radiation exposure, 15 were diabetics, seven had a diagnosis of hypothyroidism, and six were malnourished. In fact, some patients had two or more of these risk factors and thus presented with compounded risk for fistula formation . Our study also indicated that fistulas most often formed following total or partial laryngectomy or following neck dissection.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In patients undergoing treatment for fistula closure, 15 had prior radiation exposure, 15 were diabetics, seven had a diagnosis of hypothyroidism, and six were malnourished. In fact, some patients had two or more of these risk factors and thus presented with compounded risk for fistula formation . Our study also indicated that fistulas most often formed following total or partial laryngectomy or following neck dissection.…”
Section: Discussionmentioning
confidence: 51%
“…The treatment length ranged from 2 to 58 days, with follow‐up lengths between 21 days to 2 years. The two largest case series in this subgroup reported 85% and 92% successful response rates among 13 and 12 patients, respectively . There were 15 cases with radiation exposure, 15 with DM, seven with hypothyroidism, and six with malnutrition.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Asher et al analysed 12 patients who underwent laryngopharyngectomy and subsequent pharyngeal reconstruction. Seven patients developed pharyngocutaneous fistulas.…”
Section: Resultsmentioning
confidence: 99%
“…For patients with pharyngocutaneous fistulas, intraluminal NPWT is an alternative treatment method. Asher et al used intraluminal NPWT to treat seven patients with pharyngocutaneous fistulas and five other patients requiring prophylactic treatment owing to perceived high risk of fistula formation. The researchers combined a continuous negative pressure of 125 mm Hg with regional or free tissue transfer.…”
Section: Discussionmentioning
confidence: 99%